RELIGIOUS POLICY IN THE AGE OF AI: A PERSONALIST INQUIRY INTO MORAL PRAXIS AND DIGITAL TRANSFORMATION - Neonnub, Patricius; Yuda Pramana, Oktovianus (The Ministry of Religious Affairs, The Republic of Indonesia, 2025)
The rapid advancement of artificial intelligence (AI) is transforming the foundations of religious authority and ethical formation in contemporary societies. This study examines how algorithmic systems—such as chatbots, recommendation algorithms, and AI-generated sermons—reshape religious legitimacy and moral discourse. Employing a conceptual–philosophical approach grounded in personalist realism, the research integrates theological anthropology with normative policy analysis to assess the ethical implications of AI in religious life. The findings indicate that AI shifts religious authority from institutional mediation toward algorithmic visibility and data-driven influence. While this transformation democratizes access to religious knowledge, it also fragments theological coherence and weakens interpretive accountability. A central moral paradox emerges: increased participation in religious discourse coexists with diminished spiritual depth and responsibility. Ethical concerns arise from distributed agency, opaque algorithmic processes, and the reduction of human dignity to data-based representations. The study argues that prevailing regulatory frameworks, which focus primarily on technical governance and risk mitigation, are insufficient to address the deeper moral challenges posed by AI in religious contexts. It therefore proposes a shift toward a transcendental policy framework that conceives governance as moral praxis oriented toward truth, responsibility, and human flourishing. Policy recommendations include the development of a Religious Digital Ethics Framework, the establishment of a Digital Religious Ethics Council, and the integration of interfaith digital ethics education. The study concludes that religious policy must be grounded in the principle of imago Dei, ensuring that technological innovation remains subordinate to human dignity and humanity’s spiritual vocation.